Design and Implementation of a Binary Phase-Shift Keying Frequency Diverse Array: Considerations and Challenges - Nicholas R. Munson; Bill Correll; Justin K. A. Henry; Ram M. Narayanan; Travis D. Bufler (Sensors)
The frequency diverse array (FDA) is an architecture capable of beamforming in both range and angle, improving upon the traditional phased array (PA) which can only achieve beamforming in angle. The FDA employing directional modulation (DM) for secure directional communications (SDC) can reduce bit error rates (BERs) in both range and angle, again improving upon the traditional PA which can only reduce BER in angle. In this paper, we document the challenges involved in the design and implementation of a two-element linear FDA employing fast-time binary phase-shift keying (BPSK) modulations. We also show that the experimentally collected field data match well with the results of simulations based on our analytical model.